PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DENGAN MENGEMBANGKAN LKPD BERBASIS PROBLEM BASED LEARNING (PBL) KELAS 2 SEKOLAH DASAR - Susanti, Rahma; Nurhanurawati; Fatkhur Rohman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Problem Based Learning (PBL)-based Student Worksheet (LKPD) to enhance the critical thinking skills of second-grade elementary students in the topic of subtraction 1–10. The development followed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The analysis revealed that students’ critical thinking skills were still low, with most scoring below the high category. The developed LKPD was tailored to the characteristics of second graders and systematically designed based on the PBL syntax. The implementation showed a significant improvement in students’ critical thinking skills, with the average score increasing from 51.73 (pretest) to 82.52 (posttest). Statistical analysis indicated a significant difference between pretest and posttest results (p < 0.05), and the N-Gain score of 0.6292 was categorized as moderate. These findings demonstrate that PBL-based LKPD is effective in improving students’ critical thinking skills and can serve as an innovative teaching material alternative for elementary education.